The Relationship between Adolescent Attitudes and Compliance in Implementing COVID-19 Prevention Health Protocols - Girianto, Pria Wahyu Romadhon; Hayati, Farida; Puspita, Arum Dwi (Universitas Muhammadiyah Lamongan, 2022)
Introduction: Indonesia is being hit by the COVID-19 pandemic at the moment. The government established a disaster emergency status to prevent the spread of this virus by making a COVID-19 health protocol. The success of the COVID-19 health protocol depends on the attitude of the teenager and their level of compliance. This study aimed to analyze the correlation between attitude and compliance with the implementation of health protocols during the COVID-19 pandemic.Methods: Research design was correlated with a cross- sectional approach. There were 55 teenagers aged 17-20 years by purposive sampling. The instrument used for collecting attitude and compliance data was a questionnaire. The data analysis used Spearman rank.Results: The results showed that almost half of the respondents, 49.1%, had a moderate attitude and most of the respondents, 56.4%, had moderate compliance. Analysis with the Spearman rank statistical test obtained a p-value of 0.012 and an error rate of =0.05 (0.0120.05). It means that there was a correlation between attitude and compliance with implementing health protocols in teenagers aged 17–20 years, with a positive correlation and weak power category (r = 0.335).Conclusion: Attitude is sufficient to cause moderate compliance in teenagers aged 17–20 years when implementing health protocols. For this reason, hopefully the health worker will add information about COVID-19 to the community by conducting socialization about COVID-19 and health protocols.